Campanayuq Rumi and Arpiri: two civic-ceremonial centers on the southern periphery of the Chavín Interaction Sphere. (2nd January 2019) - Nesbitt, Jason; Matsumoto, Yuichi; Palomino, Yuri Cavero
Abstract : Archaeological research over the last decade has established the significance of the Peruvian south-central highlands for understanding the Chavín Interaction Sphere. Investigations at various sites in the region show distinct traditions of civic-ceremonial architecture that are in many ways comparable to better understood developments in the north-central and northern Peruvian highlands. In this paper, the authors discuss two important late Initial Period and Early Horizon centers in the region: Campanayuq Rumi and the recently discovered Arpiri. Geochemical sourcing and other lines of evidence indicate that Campanayuq Rumi was one of the major locations for the distribution of Quispisisa obsidian to the northern centers of the Chavín Interaction Sphere. However, a recent survey of the Quispisisa obsidian quarries near Huancasancos led to the discovery of Arpiri, a smaller-scale center that emulates many of the architectural conventions of Campanayuq Rumi. We hypothesize that Arpiri, which was located in close proximity to the Quispisisa quarries, was a gateway community that served to distribute obsidian to Campanayuq Rumi.